Strategi Digitalisasi Sekolah Dalam Mendukung Program Sekolah Penggerak Di SD Negeri 7 Rambutan Kabupaten Banyuasin - Endang Susilawati; Alhadi Yan Putra; Nuril Furkan (CV. Ulil Albab Corp, 2025)
This research is a qualitative study. The research subjects were the principal, teachers, learning committee, and students of SDN 7 Rambutan, Banyuasin Regency. Data was collected through observation, interviews, and document analysis. This study aimed to determine the extent to which the school's digitalization strategy supports the School Leadership Program at SDN 7 Rambutan. The research results showed that SDN 7 Rambutan has implemented a digitalization strategy based on the national School Leadership Program. Therefore, it can be concluded that the school's digitalization strategy in supporting the School Leadership Program at SDN 7 Rambutan has been implemented successfully. This is evidenced by the active involvement of the principal, teachers, learning committee, students, and parents in supporting the program and the school's recognition as an Inspirational Implementing School of the School Leadership Program by the Ministry of Education, Culture, Research, and Technology.